Kazakhstan. - Brummell, Paul, ....- (Chalfont St Peter : Bradt Travel Guides, 2011)
Landlocked between Russia and China, and surrounded by the shimmering Caspian Sea shores and the Altai and Tian Shan mountains, a trip to the exotic wilds of Kazakhstan will erase any association Westerners may have with the film Borat. Visit in May and find the slopes of the Tian Shan carpeted with tulips, base yourself in cosmopolitan Almaty and daytrip to the nearby mountains and forest (where the pious may encounter the legendary Buddhist kingdom of Shambala), or sample a glass of kumiss at a Kazakh dastarkhan. Now updated with more detail, Kazakhstan provides in-depth explanation of the rich and unique Kazakh traditions and nomadic heritage. The most comprehensive guide available, it's invaluable for anyone visiting or living in Kazakhstan.
Keywords: Kazachstan -- Reisgidsen